Synthesis of Optically Active N-(4-Hydroxynon-2-enyl)pyrrolidines: Key Building Blocks in the Total Synthesis of Streptomyces coelicolor Butanolide 5 (SCB-5) and Virginiae Butanolide A (VB-A) - Donges, Jonas; Hofmann, Sandra; Walter, Johannes C.; Reichertz, Julia; Brüggemann, Moritz; Frank, Andrea; Nubbemeyer, Udo (Synthesis, 2021)
Starting from 5-methylhexanal and (S)-configured N-propargylprolinol ethers, coupling delivered N-(4-hydroxynon-2-ynyl)prolinol derivatives as mixtures of C4 diastereomers. Resolution of the epimers succeeded after introduction of an (R)-mandelic ester derivative and subsequent HPLC separation. Alternatively, suitable oxidation gave the corresponding alkynyl ketone. Midland reagent controlled diastereoselective reduction afforded a defined configured propargyl alcohol with high selectivity. LiAlH4 reduction and Mosher analyses of the allyl alcohols enabled structure elucidation. The suitably protected products are used as key intermediates in enantioselective Streptomyces γ-butyrolactone signaling molecule total syntheses.
Keywords: propargyl alcohols; allyl alcohols; N-allylprolinol derivatives; O-acetylmandelic acid; enantioselective reduction; Mosher analysis